2014
DOI: 10.1080/09168451.2014.890037
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of peroxiredoxin isoforms in Euglena gracilis

Abstract: Euglena gracilis lacks catalase and contains ascorbate peroxidase (APX) which is localized exclusively in the cytosol. Other enzymes that scavenge reactive oxygen species (ROS) in Euglena have not yet been identified; therefore, ROS metabolism, especially in organelles, remains unclear in Euglena. The full-length cDNAs of four Euglena peroxiredoxins (EgPrxs) were isolated in this study. EgPrx1 and -4 were predicted to be localized in the cytosol, and EgPrx2 and -3 in plastids and mitochondria, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Alternative respiratory pathways are likely involved in cellular responses to oxidative stress (Castro-Guerrero et al 2004, since E. gracilis lacks catalase, but contains ascorbate peroxidase (APX), which localizes exclusively to the cytosol (Shigeoka et al 2002). Other enzymes involved in detoxification of reactive oxygen species (ROS) have not been found yet, thus little is known about ROS metabolism in Euglena (Tamaki et al 2014). Euglena was shown to contain 2-CysPrxs in the mitochondria (Castro and Tomás 2008).…”
Section: Aerobic Metabolic Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative respiratory pathways are likely involved in cellular responses to oxidative stress (Castro-Guerrero et al 2004, since E. gracilis lacks catalase, but contains ascorbate peroxidase (APX), which localizes exclusively to the cytosol (Shigeoka et al 2002). Other enzymes involved in detoxification of reactive oxygen species (ROS) have not been found yet, thus little is known about ROS metabolism in Euglena (Tamaki et al 2014). Euglena was shown to contain 2-CysPrxs in the mitochondria (Castro and Tomás 2008).…”
Section: Aerobic Metabolic Pathwaymentioning
confidence: 99%
“…Euglena was shown to contain 2-CysPrxs in the mitochondria (Castro and Tomás 2008). Tamaki et al (2014) examined four peroxiredoxins (Prx), two localized in the cytosol and the others in the plastids and the mitochondria, respectively. All could reduce both H 2 O 2 and alkyl hydroperoxide and might contribute to ROS metabolism -also in mitochondria Under aerobic conditions (shown in the upper part in red) either pyruvate from the glycolytic pathway enters the mitochondrion or malate or lactate via the lactate shuttle enter the mitochondrion, where they are converted to pyruvate.…”
Section: Aerobic Metabolic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…4.4. However, Euglena cell lines in which EgPrx2 and NTRC gene expression were individually silenced did not show any critical cell damages by oxidative stress under illumination suggesting that the thiol-redox system is not a decisive factor for ROS metabolism in Euglena chloroplasts (Tamaki et al 2014(Tamaki et al , 2015. As described in Sect.…”
Section: Ascorbate Peroxidase and Ascorbate-regenerating Systemmentioning
confidence: 86%
“…Euglena lacks APX isoenzymes in its chloroplasts raising the significant question of how Euglena metabolizes H 2 O 2 generated in these organelles. Tamaki et al (2014) reported that Euglena possesses peroxiredoxin (EgPrx2), also called thioredoxin peroxidase, in chloroplasts as well as NADPH-dependent thioredoxin reductase (type NTRC) indicating that a thiol-redox system functions to metabolize ROS in chloroplasts replacing the AsA-GSH cycle (Fig. 4.2).…”
Section: Ascorbate Peroxidase and Ascorbate-regenerating Systemmentioning
confidence: 99%